Au coated etched FBG SPR sensor for the detection of ethanol in aqueous solution - Thirunavakkarasu, Punithavathi M.; Khan, Abdul Ali; Muhammad Noor, Ahmad Shukri; Saidin, Norazlina; Waqas, Nawaf (Elsevier, 2023)
Over the past few years, there has been a growing need for reliable ethanol sensors in the pharmaceutical and food industries. These industries require constant monitoring to ensure that the acceptable ethanol levels are maintained. This study reports a new fiber optic sensor that uses etched single mode fiber Bragg grating (FBG) coated with the thin layer of 45 nm gold to produce Surface Plasmon Resonance (SPR). A thin layer of 45 nm gold improves the sensitivity of sensor by improving the evanescent wave around the fiber, resulting in better interaction with the analyte. The sensing performance of developed structure was examined by analyzing the change in wavelength shift observed by varying ethanol concentration in aqueous solution from 0 to 100 . The performance of developed sensor in terms of sensitivity is 20 pm/RIU. Which is expected to play an important role in food and pharmaceutical industries to protect human health from detrimental affects due to high concentration of ethanol.